2007
DOI: 10.1089/hum.2006.082
|View full text |Cite
|
Sign up to set email alerts
|

Spatial And Temporal Expression of Herpes Simplex Virus Type 1 Amplicon-Encoded Genes: Implications for Their Use As Immunization Vectors

Abstract: There is great interest in developing new immunization vectors. Helper virus-free herpes amplicons, plasmid-based vectors that encode no viral gene products and have an extremely large coding capacity, are attractive viral vaccine candidates for expressing recombinant proteins in vivo for immunization. Earlier studies in mice, using amplicons encoding the gp120 protein of human immunodeficiency virus (HIV), resulted in strikingly robust cellular immune responses as measured by cytotoxicity and interferon gamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 68 publications
1
13
0
Order By: Relevance
“…This is consistent with the changes in the functional signatures of antigenspecific CD4 + T cells that occur over time, in response to cell differentiation, establishment of immune memory, and changes in antigen load [33,46]. HSV-1 amplicon vectors are known to elicit a sharp, acute burst of antigen exposure that is extinguished within a week following vector delivery [22], while adenovirus vectors may continue to produce low levels of antigen over a protracted period [59]. Thus, the broad similarity in the functional CD4 + T cell profiles elicited by these vectors at both the effector (day 12; Figure 2) and memory phases (day 84; "prime only" groups, Figure 4) is of interest.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…This is consistent with the changes in the functional signatures of antigenspecific CD4 + T cells that occur over time, in response to cell differentiation, establishment of immune memory, and changes in antigen load [33,46]. HSV-1 amplicon vectors are known to elicit a sharp, acute burst of antigen exposure that is extinguished within a week following vector delivery [22], while adenovirus vectors may continue to produce low levels of antigen over a protracted period [59]. Thus, the broad similarity in the functional CD4 + T cell profiles elicited by these vectors at both the effector (day 12; Figure 2) and memory phases (day 84; "prime only" groups, Figure 4) is of interest.…”
Section: Discussionsupporting
confidence: 78%
“…For these experiments, we chose to allow primed mice to 'rest' for 72 days before boosting. Since HSV-1 amplicon vectors induce high and transient levels of transgene (antigen) expression [22], we expected that the overwhelming majority of antigen specific T cells present at the time of the boost would therefore be memory cells. This prediction was consistent with the strikingly polyfunctional nature of the CD4 + T-cell population in mice that received only a priming immunization with HSV-1 amplicon or rAd5 vectors (and no boost).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transduced vector genome and expression titers were determined at 48 h post-transduction using NIH 3T3 cells, when the CMV promoter in the context of an amplicon vector is maximally expressed (Bowers and Federoff, unpublished observations, and [25]). Removal of HMBA from the amplicon packaging procedure resulted in a marked increase in expression titers, while transduced vector genome titers remained unchanged (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In a study conceived to investigate how amplicon vectors function in vivo to generate an immune response, amplicon vectors expressing either GFP or luciferase reporter proteins were used to examine the duration of expression after administration to mice [46]. Injection with amplicons expressing luciferase revealed that transgene expression peaked earlier than 24 hr after injection in mice.…”
Section: Constitutive Antiviral Responses Can Inhibit Amplicon-mediatmentioning
confidence: 99%